Pengaruh Subtitusi Getah Damar Terhadap Aspal Pen 60/70 Sebagai Modifikasi Untuk Lapisan Aspal Beton - Munawarah; Febrina Dian Kurniasari; Bunyamin (Jurnal Perencanaan dan Penelitian Teknik Sipil, 2022)
The construction of highways in Indonesia generally uses flexible pavement, modifying asphalt with resin resin which is used to substitute asphalt on concrete asphalt layers The aim of this research is to find out whether resin resin can be used as a mixture substitute (AC-WC). The scope of this study is the collection of resin resin from the village of Lhok Seumot Kec, Beutong, Nagan Raya Regency, the material used in this study was taken from PT. Dana Dinamika Persada which is located in Aceh Besar. The method used in this research is the wet method which refers to the 2010 revision 4 (2018) Highways specifications. marshall characteristic testing was carried out at 5 (five) asphalt content to determine the optimum asphalt content (KAO). 4.5%, and 5.5%. The research results obtained for the best substitution were 1.5% resin resin percentage with aspa content; 5.00% obtained a VIM value of 4.57% VMA 16.41% VFA 72.29% Stability 1006.87kg and Flow 2.467mm, all values ??meet the specifications specified by Bina Marga 2010 revision 4 (2018)